Through Music to Power: Musical Offices as a Strategy for Political Advancement in the Monastery of St. Catherine of Siena (Córdoba, 18th Century) (Revista Argentina de Musicología, 2019)
We have been able to identify, after laborious tracing, the webs of kinship within the higher ranks of the monastery as well as their links to those that held positions of power in the city. As a result, we detected a narrow circle of nuns that held in their hands the guidance of the institution: the prioress and the members of her council. They monopolized government, both in spiritual and in material matters. To join the group that ruled the monastery, one had to begin by the appointment to several offices, the importance of which was set in a hierarchical order.In this paper we propose that the offices of cantora and subcantora [leader of the choir and assistant leader] constituted rungs which a nun could occupy in order to further her ascent in the ladder towards power in the convent’s government. We thus suggest that musical function constituted an important link in the power relationships that echoed within the convent the same structures that obtained without.
Keywords: Córdoba del Tucumán; Saint Catherine of Siena; Nuns; Cantoras y Subcantoras